Association of Ipsilateral Rib Fractures With Displacement of Midshaft Clavicle Fractures. Issue 4 (April 2017) - Stahl, Daniel; Ellington, Matthew; Brennan, Kindyle; Brennan, Michael
Abstract : Objectives: To determine whether the presence of ipsilateral rib fractures affects the rate of a clavicle fracture being unstable (>100% displacement). Design: A retrospective review from 2002–2013 performed at a single level 1 trauma center evaluated 243 midshaft clavicle fractures. Setting: Single Level 1 trauma center. Patients/Participants: These fractures were subdivided into those with ipsilateral rib fractures (CIR; n = 149) and those without ipsilateral rib fractures (CnIR; n = 94). Intervention: The amount of displacement was measured on the initial injury radiograph and subsequent follow-up radiographs. Main Outcome Measurements: Fractures were classified into either <100% displacement or >100% displacement, based on anteroposterior radiographs. Ipsilateral rib fractures were recorded based on which number rib was fractured and the total number of fractured ribs. Results: One hundred sixteen (78%) of the CIR group and 51 (54%) of the CnIR group were found to have >100% displacement at follow-up ( P = 0.0047). Seventy-two percent of the CIR group demonstrated progression from <100% to >100% displacement of the fracture compared with only 54% of the CnIR group ( P < 0.05). The odds ratio for progression of the clavicle fracture to >100% was 4.08 ( P = 0.000194) when ribs 1–4 were fractured and not significant for rib fractures 5–8 or 9–12. Conclusions: The presence of concomitant ipsilateral rib fractures significantly increases the rate of midshaft clavicle fractures being >100% displaced. In addition, a fracture involving the upper one-third of the ribs significantly increases the rate of the clavicle fracture being >100% displaced on early follow-up. Clavicle fractures with associated ipsilateral rib fractures tend to demonstrate an increased amount of displacement on follow-up radiographs compared with those without ipsilateral rib fractures. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.